Influence of a special training process on the psychomotor skills of cadet pilots – Pilot study - Prokopczyk, Adam; Wochyński, Zbigniew (Frontiers in Psychology, 2022)
Objectives: The aim of the study was to check the influence of the training process on the Special Aviation Gymnastics Instruments (SAGI) on the improvement of the psychomotor skills, expressed as an increase in the percentage of ability to perform all tasks and the number of reels on a loop. Methods: Cadets - second year pilots (n=20), male, mean age 20.8 years old, studying at the faculty of a pilot. Cadets were carrying out a 40-hour special pilot training program on SAGI. They were subjected to two exercise tests (reels forward on looping), before and after the period of special training. Exercise tests were performed with the use of a diagnostic and training device used to assess psychomotor skills. During two tests, heart rate (HR) and blood pressure were measured. The obtained results were analysed statistically. Results: There was a statistically significant increase in the percentage of ability to perform all tasks (p<0.01) and a statistically insignificant increase in the number of reels forward on looping, in test II in relation to test I. A significant increase was found in the correct execution of arithmetic operations (p<0.05) in test II in relation to test I. In the remaining tests, an increase in results in test II was noted, but it was not statistically significant. There was a significant correlation between the percentage ability to perform all tasks and the number of completed reels in test I (p<0.05) and insignificant in test II. In test II, a statistically insignificant higher level of heart rate and blood pressure before and after the effort was noted, compared to test I. Conclusions: It was found that the training process on SAGI increased the psychomotority level by increasing the percentage of ability to perform all tasks and the number of reels, in test II in relation to test I.